2021
DOI: 10.3892/or.2021.7996
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0000003 regulates glutamine metabolism and tumor progression of tongue squamous cell carcinoma via the miR‑330‑3p/GLS axis

Abstract: Various circular RNAs (circRNAs) have been shown to exert vital functions in tongue squamous cell carcinoma (TSCC). However, their roles in TSCC progression remain to be elucidated. This research aimed to investigate the role and mechanism of hsa_circ_0000003 (circ_0000003) in TSCC progression. Here, we found that circ_0000003 expression was upregulated in TSCC tissues and cell lines, and high circ_0000003 expression was correlated with advanced TNM stage, increased tumor size and poor patient survival. Circ_0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Finally, 55 articles that involved details regarding 56 unique circRNAs and 5,576 HNSCC cases (all cases were reliably diagnosed via histopathological analysis) were included in this meta‐analysis. To be specific, we included 31 diagnostic studies (from 23 articles 25–47 ), 38 prognostic studies (from 38 articles 25–30,48–79 ), and 27 clinical‐pathological feature‐related studies(from 26 articles 28,29,43,47,48,50,51,53,55,56,58,63–68,70–74,76–79 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 55 articles that involved details regarding 56 unique circRNAs and 5,576 HNSCC cases (all cases were reliably diagnosed via histopathological analysis) were included in this meta‐analysis. To be specific, we included 31 diagnostic studies (from 23 articles 25–47 ), 38 prognostic studies (from 38 articles 25–30,48–79 ), and 27 clinical‐pathological feature‐related studies(from 26 articles 28,29,43,47,48,50,51,53,55,56,58,63–68,70–74,76–79 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, there are few articles on HNSCC tumors in these meta-analyses. A growing number of studies have shown that some circRNAs are abnormally expressed in HNSCC 32,37,39,[65][66][67][68] . However, the predictive value of circRNAs in HNSCC is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CDKN2A is considered a common mutation of the tumor suppressor and checkpoint mediator in HPV-negative HNSCC (26). GLS can facilitate HNSCC cell proliferation, migration, invasion and glutamine catabolism by regulating hsa-circ-0000003 via the miR-330-3p/GLS pathway (27). Furthermore, hsa-miR-124-3p (28) and hsa-miR-488-3p (29) were also determined to play crucial roles in HNSCC and other tumors according to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of circ0000003 in ESCC was reported to be correlated with advanced TNM stage and increased tumor size. Overexpression of circ0000003 has been shown to promote cell proliferation, whereas circ0000003 knockdown significantly inhibited cell invasion and migration ( 129 ).…”
Section: Other Types Of Tumorsmentioning
confidence: 99%
“…In TSCC, circ0000003 upregulates the expression of GLS to promote glutaminase expression and cell proliferation by sponging miR−330−3p. Meanwhile, the miR−330−3p inhibitor has been shown to reverse the above downgrading effects ( 129 ). Similarly, circ-OGDH has been shown to elevate glutamine metabolism by sponging miR-615-5p to release PDX1.…”
Section: Circrnas Regulate Energy Metabolism In the Tmementioning
confidence: 99%